Comprehensive expression analysis of mRNA and microRNA for the investigation of compensatory mechanisms in the rat kidney after unilateral nephrectomy. Issue 10 (5th May 2020) - Matsushita, Kohei; Toyoda, Takeshi; Yamada, Takanori; Morikawa, Tomomi; Ogawa, Kumiko
Abstract: Compensation is a physiological response that occurs during chemical exposure to maintain homeostasis. Because compensatory responses are not usually considered adverse effects, it is important to understand compensatory mechanisms for chemical risk assessment. Although the kidney is a major target organ for toxicity, there is controversy over whether hyperplasia or hypertrophy contributes to the compensatory mechanism, and there is limited information to apply for chemical risk assessment. In the present study, compensatory mechanisms of the kidney were investigated in a unilateral nephrectomy (UNx) model using adult male and female F344 rats. In residual kidneys of male and female rats after UNx, 5‐bromo‐2′‐deoxyuridine‐labeling indices and mRNA expression of cell cycle‐related genes were increased, although there were no fluctuations in mRNA expression of transforming growth factor‐β1, which contributes to hypertrophy in renal tubules. Pathway analysis using mRNA expression data from a complementary DNA (cDNA) microarray revealed that canonical pathways related to cell proliferation were mainly activated and that forkhead box M1 (FOXM1) was an upstream regulator of compensatory cell proliferation in residual kidneys of male and female rats. cDNA microarray for microRNAs (miRNAs) demonstrated that nine miRNAs were downregulated in residual kidneys, and mRNA/miRNA integrated analysis indicated that miRNAs were associated with the expression of factors downstream of FOXM1. Overall, these results suggested that FOXM1‐mediated hyperplasia rather than hypertrophy contributed to compensatory mechanisms in the kidney and that miRNAs regulated downstream FOXM1 signaling. These results will be beneficial for evaluating nephrotoxicity in chemical risk assessment and for developing new biomarkers to predict nephrotoxicity. Abstract : Because compensatory responses are not considered adverse effects, it is important to understand compensatory mechanisms for chemical risk assessment. We investigated compensatory mechanisms in the kidney by comprehensive analysis of mRNA and microRNA in a rat unilateral nephrectomy model. Overall, the results indicated that FOXM1‐mediated hyperplasia contributed to compensatory mechanisms in the kidney and miRNAs regulated downstream FOXM1 signaling. These results will be beneficial for evaluating nephrotoxicity in chemical risk assessment and for developing new biomarkers of nephrotoxicity.